2011
DOI: 10.1016/j.math.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a musculoskeletal masters course: Developing clinical expertise

Abstract: a b s t r a c t A common aim of Masters (MSc) courses in the UK, accredited by the Manipulation Association of Chartered Physiotherapists (MACP), is to promote the clinical expertise of practitioners. Few studies have explored the extent to which this is achieved and understanding is further hampered by the contested nature of expertise. This paper reports on the impact of an MACP approved MSc on practitioners and offers a conceptual model of their development towards clinical expertise.A qualitative theory-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…In this current study, no relationship between participants' years of clinical experience and their conception of practice was found. This finding is consistent with existing research (Resnik and Hart, 2003;Resnik and Jensen, 2003;Petty et al, 2011a), and theories of expertise (Schön, 1987;Eraut, 1994), thereby supporting the notion that the development of clinical expertise and artistry, is not related to years of experience (Richardson, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…In this current study, no relationship between participants' years of clinical experience and their conception of practice was found. This finding is consistent with existing research (Resnik and Hart, 2003;Resnik and Jensen, 2003;Petty et al, 2011a), and theories of expertise (Schön, 1987;Eraut, 1994), thereby supporting the notion that the development of clinical expertise and artistry, is not related to years of experience (Richardson, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…24 Later, in the 1980s, medical researchers began focusing on the different ways in which expert physicians organised and structured their knowledge in relation to their diagnostic reasoning. Groen and Patel 25 identified that during non-problematic situations, experts did not rely solely on hypotheticod The concept of the 'expert' is problematic, and researchers currently have a limited understanding of the nature of expertise in healthcare (for example see, Mylopoulos et al, 20 Jensen et al 21,22 and Petty et al 23 ).…”
Section: The Development Of Diagnostic Reasoning Researchmentioning
confidence: 99%
“…Furthermore, in taking a grounded theory approach, this research followed in the footsteps of researchers in the physiotherapy profession who used grounded theory to help understand clinical expertise and decision-making. 57e59, 72,73 The main methodological processes used in grounded theory (Fig. 1) are now discussed with reference to the case example.…”
Section: Discussionmentioning
confidence: 99%